Technostress among marketing employee during the COVID-19 pandemic: Exploring the role of technology usability and presenteeism - Khuzaini, Khuzaini; Zamrudi, Zakky (University of Islam Malang, 2021)
The COVID-19 pandemic is profoundly affecting the way of consumer buying. Firms are therefore challenged to be more reliant on technology as many consumers have turned into protection mode and do anything remotely. While the usage of technology has offered flexibility and simplicity, it has also exacerbated the technostress issue. This study was conducted to understand and examine technology usability and presenteeism that influence technostress during the COVID-19 pandemic situations. A five-point Likert scale questionnaire survey was used to evaluate the perceptions of technology characteristics and techno-stress among marketing employees. A total of 262 respondents that classified as marketing employees that are experienced â€œworking from homeâ€ during the pandemic, were collected and analyzed by using Covariance Based Structural Equation Modeling (CB-SEM). The results suggest that technology usability has positive influences on techno-complexity and techno-insecurity. Moreover, the negative influences of presenteeism on techno-overload and techno-insecurity were also proved in this study. Interestingly, marketing employees do not see their hyper-connectivity with technology implemented by the company impact their workloads and worries as they consider the current radical changes only temporary and will only last during the pandemic.